Test derivation based on tree FSMs and tree automata - Maria Forostyanova (Труды Института системного программирования РАН, 2018)
In this paper, an approach for testing software implementations of telecommunication protocols based on tree finite state machines (FSM) is proposed. The first step is the extraction of the specification Extended FSM from an informal protocol description. The next step is to derive a corresponding EFSM l-equivalent that is a tree FSM. Based on the set of considered faults corresponding sequences of the l-equivalent are included into a test suite. The proposed approach is illustrated by protocol TCP (Windows).